Perlocutionary Act of Euphemism in Indonesian Presidential Election Debate 2019 - Wahyuningsih Wahyuningsih; Deli Nirmala (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2020)
Presidential election debate attracts public attention toward general election. Through the presidential debate, euphemism is uttered by candidates, and it creates effect to other debaters. This paper is focused on examining effect (perlocutionary act)of euphemism in presidential election debate 2019. The corpus covers the utterances containing euphemism and their responses as the effect produced by the candidates in the prime presidential election debate 2019. The methods used in analyzing data were pragmatics identity method and referential method. The results show that the effect of using euphemism includes verbal perlocutionary act acceptance namely agreement and verbal perlocutionary act refusal includes contradiction, rebuttal, disagreement, denial and criticism. Verbal perlocutionary act acceptance is only expressed by a candidate from the same party as support. However, the verbal perlocutionary act of refusal is expressed by candidates respectively. It indicates that each candidate has different ideology and communication strategy.